A reason open to God : on universities, education, and culture - Benedict XVI, Pope, 1927-2022 (UPCC book collections on Project MUSE., 2013)
A collection of Pope Benedict XVI's addresses on the topic of higher education. This collection addresses these questions: What is the mission and identity of a Catholic university? What are the responsibilities of administrators, teachers, and students in Catholic institutes of higher learning? Where does the central theme of "love of God and others" fit into academia? -- Adapted from book flap description.